Didactical Design Research (DDR) With Translation Module Development in Elementary Schools and Junior High Schools - Jitu Halomoan Lumbantoruan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The thinking process carried out by teachers occurs in three phases, namely before learning, during learning, and after learning. The results of the analysis of these processes have the potential to produce innovative didactic designs, and these three processes can be formulated as a series of steps to produce new didactic designs. This series of activities is formulated as Didactic Design Research (DDR). Didactic Design Research basically consists of three stages, namely: (1) analysis of the didactic situation before learning which is in the form of a Hypothetical Didactic Design including ADP, 2) metapedidactic analysis, and 3) retrospective analysis, namely an analysis that links the results of the analysis of the hypothetical didactic situation with the results of the metapedidactic analysis. From these three stages, an Empirical Didactic Design will be obtained which is not closed to being continuously refined through the three stages of DDR.